Emerging roles for TFEB in the immune response and inflammation - Brady, Owen A. (Autophagy, 2017)
Inflammation is a central feature of an effective immune response, which functions to eliminate pathogens and other foreign material, and promote recovery; however, dysregulation of the inflammatory response is associated with a wide variety of disease states. The autophagy-lysosome pathway is one of 2 major degradative pathways used by the cell and serves to eliminate long-lived and dysfunctional proteins and organelles to maintain homeostasis. Mounting evidence implicates the autophagy-lysosome pathway as a key player in regulating the inflammatory response; hence many inflammatory diseases may fundamentally be diseases of autophagy-lysosome pathway dysfunction. The recent identification of TFEB and TFE3 as master regulators of macroautophagy/autophagy and lysosome function raises the possibility that these transcription factors may be of central importance in linking autophagy and lysosome dysfunction with inflammatory disorders. Here, we review the current state of knowledge linking TFEB and TFE3 to the processes of autophagy and inflammation and highlight several conditions, which are linked by these factors.